Fabrication of polyethylene nanofibrous membranes by biaxial stretching. (December 2018) - Wan, Caixia; Cao, Tian; Chen, Xin; Meng, Lingpu; Li, Liangbin
Graphical abstract: Highlights: A kind of nanofibrous membranes is prepared by biaxial stretching of polyethylene. The membranes are composed of nanofibrous scaffold with fiber diameters of 30 nm–40 nm and fully interconnected pores. The mechanical strength of nanofibrous membranes are raised by one magnitude compared to electronspun nanofibrous membranes. The nanofibrous membranes could reject the molecules with Mw larger than 100 kDa efficiently with moderate water permeance. Abstract: Polyethylene (PE) nanofibrous membranes are fabricated via sequential biaxial stretching with carefully selected processing conditions, which are featured by excellent morphology with fine fibers and homogeneously distributed pores as well as good mechanical properties. The orientation of fibers along draw ratios is inspected by wide angle X-ray scattering (WAXS). Morphologies of the samples are characterized by scanning electron microscopy (SEM). The membranes are composed of nanofibrous scaffold with fiber diameters of 30 nm–40 nm and fully interconnected pore structures with mean pore size between 19 nm and 26 nm, respectively. The mechanical and separation properties are measured. The maximum Young's modulus and tensile strength of this membranes are 1186 MPa and 154 MPa, respectively, about 10 times that of conventional electrospun nanofibrous membranes. The separation test exhibits that the membranes can reject the molecules with molecular weight larger than 100 kDa efficiently with moderate water permeance. The as prepared membranes show potential in microfiltration applications.